Enhancing entrepreneurial intentions among vocational high school students - Devi Rosniawati; Yunizar Yunizar (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study investigates the determinants of entrepreneurial intentions among vocational high school students, focusing on the roles of entrepreneurial education, family support, and school support, with entrepreneurial self-efficacy as a mediating variable. Employing a quantitative approach with cross-sectional design. Data were collected from 214 students in the Business and Marketing Department of Vocational High School, Indonesia. The instrument that used in this research is entrepreneurial intention. For data analysis, the study utilized Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that school support significantly influences entrepreneurial intentions, with entrepreneurial self-efficacy acting as a key mediator between external support systems and entrepreneurial aspirations. Interestingly, while school support demonstrates the strongest direct impact on entrepreneurial intentions, its mediated effect through self-efficacy is comparatively smaller. The study underscores the importance of robust educational frameworks, family encouragement, and institutional facilitation in nurturing entrepreneurial mindsets. Practical implications include curriculum enhancement, teacher training in entrepreneurship education, and fostering collaborative support systems between families and schools. This research contributes to the literature by offering a comprehensive model of entrepreneurial intention formation in the context of vocational education, particularly in emerging economies